Efektivitas Model Pembelajaran Think Pair Share (TPS) terhadap Kemampuan Menghafal Al-Qur’an Peserta Didik: Penelitian - Suhada, Rahmat Ikhlas Randi Putra; Baharudin, Baharudin; Hasanah, Uswatun (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aimed to examine the effectiveness of the Think Pair Share (TPS) learning model on students’ ability to memorize the Qur’an at MTs Negeri 2 Bandar Lampung. The research was motivated by the limited effectiveness of conventional memorization methods, which tend to be monotonous and provide minimal student interaction. This study employed a quantitative approach with a quasi-experimental design of the pretest–posttest control group type. The subjects consisted of 65 students, with class VIII B assigned as the experimental group and class VIII C as the control group, selected using random sampling techniques. Data were collected through memorization tests, observations, and documentation, and analyzed using normality tests, homogeneity tests, paired sample t-tests, and N-Gain analysis. The findings revealed a significant improvement in students’ Qur’an memorization ability in the experimental group, indicated by a significance value of < 0.001 and an average N-Gain score of 0.5008, categorized as moderate effectiveness. These results indicate that the Think Pair Share (TPS) model effectively enhances students’ Qur’an memorization skills by fostering an active, collaborative, and interactive learning environment.